IMPLEMENTASI PENDEKATAN SUPERVISI DIREKTIF DALAM MENINGKATKAN PROFESIONALISME GURU MI NURUL JADID - Khoirotun Nisail Fitri; Ashari (LPPM IAI Almuslim Aceh, 2025)
This study aims to analyze the implementation of the directive supervision approach to enhance teacher professionalism at MI Nurul Jadid. The research methods used are literature review and in-depth interviews with the school principal and teachers. The research results show that the directive supervision approach is able to provide concrete guidance to teachers, thereby enhancing their professional competence. This approach involves steps such as providing direct guidance, conducting evaluations, and offering guidance tailored to the specific needs of teachers. Although effective, this approach has limitations, such as the lack of development of teacher creativity. The implications of this study indicate the need for the development of an adaptive and integrative supervision model.